Difficulties in organizing first indoor spray programme against malaria in Angola under the President's Malaria Initiative - Martinho Somandjinga; Manuel Lluberas; William R Jobin
PROBLEM: Successful attempts to control malaria require understanding of its complex transmission patterns. Unfortunately malaria transmission in Africa is often assessed using routine administrative reports from local health units, which are plagued by sporadic reporting failures. In addition, the lack of microscopic analyses of blood slides in these units introduces the effects of many confounding diseases. APPROACH: The danger of using administrative reports was illustrated in Angola, the first country in which malaria control was attempted under the President's Malaria Initiative, a development programme of the Government of the United States of America. LOCAL SETTING: Each local health unit submitted monthly reports indicating the number of suspected malaria cases to their municipality. The identification of the disease was based on clinical diagnoses, without microscopic examination of blood slides. The municipal and provincial reports were then passed on to the national headquarters, with sporadic reporting lapses at all levels. RELEVANT CHANGES: After the control effort was completed, the defective municipal reports were corrected by summarizing only the data from those health units which had submitted reports for every month during the evaluation period. LESSONS LEARNED: The corrected data, supplemented by additional observations on rainfall and mosquito habitats, indicated that there had probably been no malaria transmission before starting the control operations. Thus the expensive malaria control effort had been wasted. It is unfortunate that WHO is also trying to plan and evaluate its malaria control efforts based on these same kinds of inadequate administrative reports.